Reseña de D'Amico, C. (2023). Hildegarda de Bingen. Filósofa de lo invisible. Buenos Aires, Galerna, 230 páginas - Martínez, Emilio Nahuel (2024)
Reseña de D'Amico, C. (2023). Hildegarda de Bingen. Filósofa de lo invisible.